THE EFFECT OF USING NEWSPAPER ARTICLES IN CLASSROOM - Zamira Tenelova (Лучшие интеллектуальные исследования, 2024)
Annotation: The article deals with the experiment that we have conducted at the lyceum under the Karakalpak State University named after Berdakh and effectively utilized newspaper materials in the classroom to enhance learning, promote critical thinking, and foster engagement with real-world issues and events.